Effects of Mindfulness Based Stress Reduction Therapy on Subjective Bother and Neural Connectivity in Chronic Tinnitus. (May 2015) - Roland, Lauren T.; Lenze, Eric J.; Hardin, Frances Mei; Kallogjeri, Dorina; Nicklaus, Joyce; Wineland, Andre M.; Fendell, Ginny; Peelle, Jonathan E.; Piccirillo, Jay F.
Objective: To evaluate the impact of a Mindfulness Based Stress Reduction (MBSR) program in patients with chronic bothersome tinnitus on the (1) severity of symptoms of tinnitus and (2) functional connectivity in neural attention networks. Study Design: Open-label interventional pilot study. Setting: Outpatient academic medical center. Subjects: A total of 13 adult participants with a median age of 55 years, suffering from bothersome tinnitus. Methods: An 8-week MBSR program was conducted by a trained MBSR instructor. The primary outcome measure was the difference in patient-reported tinnitus symptoms using the Tinnitus Handicap Index (THI) and Tinnitus Functional Index (TFI) between pre-intervention, post-MBSR, and 4-week post-MBSR assessments. Secondary outcomes included change in measurements of depression, anxiety, mindfulness, and cognitive abilities. Functional connectivity magnetic resonance imaging (MRI) was performed at pre- and post-MBSR intervention time points to serve as a neuroimaging biomarker of critical cortical networks. Results: Scores on the THI and TFI showed statistically significant and clinically meaningful improvement over the course of the study with a median ΔTHI of −16 and median ΔTFI of −14.8 between baseline and 4-week follow-up scores. Except for depression, there was no significant change in any of the secondary outcome measures. Analysis of the resting state functional connectivity MRI (rs-fcMRI) data showed increased connectivity in the post-MBSR group in attention networks but not the default network. Conclusion: Participation in an MBSR program is associated with decreased severity in tinnitus symptoms and depression and connectivity changes in neural attention networks. MBSR is a promising treatment option for chronic bothersome tinnitus that is both noninvasive and inexpensive.